A nonlinear model for a three-phase 12/8 switched reluctance machine - Dimitar Kirov Yankov; Tsvetana Grigorova Grigorova (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The paper presents a methodology for the synthesis of a nonlinear model for a three-phase 12/8 switched reluctance machine (SRM) in a MATLAB/Simulink environment. The required switched reluctance motor characteristics are derived using the finite element analysis (FEA). Graphical and tabular results of the relations flux/current/position, current/torque/position, and inductance/current/position used to create the SRM model are presented. The structure of the nonlinear three-phase 12/8 SRM model is discussed and its implementation in Simulink is presented. A series of simulation and experimental results are performed to verify the accuracy of the built three-phase, 12/8 SRM (H55PWBKM-1844) nonlinear model. A very good alignment between simulation and experimental results is observed.